PERAN BANK SAMPAH TEMATIK BUMI BEKO LESTARI DESA BUMIWANGI DALAM MENGELOLA SAMPAH MENJADI RUPIAH: Role Of The Bumi Beko Lestari Thematic Waste Bank Bumiwangi Village In Managing Waste Into Rupiah - Faiz Karim, Faiz Karim Fatkhullah; Hendi S. Muchtar; Farhan; Fini Himatul Aliyah; Wafa Tsamrotul Fuadah (Forind Press, 2023)
Waste is not a source of problems but a potential environmental resource. There are still relatively many Indonesian people who do not understand waste processing. Only a small number of community groups care and are responsive to waste problems. Bumi Beko Lestari Thematic Waste Bank (BST BBL) is a group of people who have succeeded in turning waste into blessings. Even though its operations are still at the community unit (RW) area level, its business from household rubbish can bring in large sums of rupiah. Maggot, kasgot, and paving blocks are superior products produced by BST BBL. In fact, his business was flooded with orders because there were people who ordered several kilos of maggots but could not be served due to limited resources and funds. Likewise, when someone requests a relatively large quantity of plastic paving block orders, it cannot be fulfilled due to limited equipment. This service aims to strengthen the community's way of thinking about waste management which can bring economic benefits, providing assistance so that BST BBL can improve its quality, both services and products. The activity steps begin with a waste management strengthening workshop involving local residents and students and assistance to BST BBL with the hope that the quality of service and production can be maintained by implementing technology in the form of a faster and more precise plastic melting machine. In conclusion, the public is increasingly aware of the waste that can bring in rupiah and BST BBL can operate more quickly in processing waste into paving blocks.